2020
DOI: 10.3390/ijerph17228442
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and Pain Intensity in Women with Fibromyalgia: Its Influence on Activity Avoidance from The Contextual Perspective

Abstract: Given the scarcity of studies regarding perfectionism from a contextual perspective, this study aims to analyze its role in the relationship between pain and activity avoidance and its differential effect among patients with different fibromyalgia severity. A cross-sectional study with 228 women with fibromyalgia classified into two disease severity groups (low/moderate vs. high) was carried out. Moderation analyses were conducted; perfectionism was used as moderator, pain (in high and low pain situations) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Considering that perfectionism is associated with higher psychological distress [ 33 ], pain-related TMD patients may be more susceptible to negative consequences. Sheila et al reported that, in women with fibromyalgia, maladaptive perfectionism is associated with activity avoidance regardless of the degree of severity of the disease and the pain experienced in the situation, reducing the patients' ability to work and participate in social activities [ 34 ]. Therefore, perfectionism might be a target when cognitive behavioral therapy is undergone to manage pain in TMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that perfectionism is associated with higher psychological distress [ 33 ], pain-related TMD patients may be more susceptible to negative consequences. Sheila et al reported that, in women with fibromyalgia, maladaptive perfectionism is associated with activity avoidance regardless of the degree of severity of the disease and the pain experienced in the situation, reducing the patients' ability to work and participate in social activities [ 34 ]. Therefore, perfectionism might be a target when cognitive behavioral therapy is undergone to manage pain in TMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to establish mechanisms affecting activity in specific and common situations from the motivational perspective of goal conflict, taking into consideration fatigue as a disabling and forgotten symptom. 63,64 Furthermore, the study included different types of measurements, such as self-reports and objective measures, a common request in this field 35 since they increase the ecological validity of studies. In addition, another of the study's strengths is measuring walking using the 6MWT, as it is recommended by the Spanish Society of Rheumatology for Fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have received attention in previous research as mentioned, but connecting them was a pending issue. This study aimed to establish mechanisms affecting activity in specific and common situations from the motivational perspective of goal conflict, taking into consideration fatigue as a disabling and forgotten symptom 63,64. Furthermore, the study included different types of measurements, such as self-reports and objective measures, a common request in this field35 since they increase the ecological validity of studies.…”
Section: Discussionmentioning
confidence: 99%